Mitigation of 3-MCPDE and GE in palm oil in Indonesia - Jenny Elisabeth (Menara Perkebunan, 2023)
Among consumed-vegetable oils, RBDPO (refined, bleached and deodorized palm oil) is indicated containing higher level of 3-MCPDE and GE, which have been classified as potentially carcinogenic and/or genotoxic to human. Those contaminants in RBDPO are formed during deodorization process with high temperature and also correlate with chloride content and quality of CPO as raw material.  The maximum limit for 3-MCPDE and GE content in vegetable oil has been set at 2500 and 1000 µg kg-1, and as low as 750 and 500 µg kg-1 when used for production of baby food and cereal-based foods for infants and young children. The mitigation of 3-MCPDE and GE in RBDPO is quite challenging for palm oil refineries in producing a good quality of palm oil in term of sensory, stability, safety, and nutritional value, especially in Indonesia.  It has been proven that modification of conventional refining process can reduce the 3-MCPDE and GE content. They are including pre-treatment of CPO by water washing to reduce the chloride content, alkali neutralization to remove any acids present in the oil prior to deodorization, using neutral bleaching earth, adding antioxidants after bleaching to reduce free radical-mediated formation of 3-MCPDE and GE, lowering the deodorization temperature with a longer time, and even double bleaching and/or double deodorization of the palm oil.  Post-refining treatment using specific adsorbents is also applied to remove the 3-MCPDE  and GE. However, palm oil  refineries  have  to  apply combination of several mitigation strategies to adequately reduce the levels of 3-MCPDE and GE, including using good quality of CPO with low FFA, chloride, and oxidized components content.